Otak dan Akal dalam Kajian Al-Quran dan Neurosains - Ahmat Miftakul Huda; Suyadi (Program Pascasarjana Universitas Ibrahimy, 2020)
Humans are the perfect creation of Allah SWT. It lies within their mind. Moreover, they also have the brain as a control center for all human activities. This article aims to explain the concepts of al-quran and neuroscience as well as the study of the brain and mind in al-quran and neuroscience. The approach used was qualitative of Creswell model library research. Data sources were obtained from the literature in the fields of the brain and mind, al-quran and neuroscience. Data collection techniques had used Sugiyono model. The data analysis technique had used Moleong analysis model. The results of this study indicated that if humans use their brains and mind to think properly and correctly, they would be able to provide and to create new ideas in solving various problems. After humans are even more aware, they would increase the faith and devotion to Allah.